2020
DOI: 10.1002/admt.202000180
|View full text |Cite
|
Sign up to set email alerts
|

Bismuth Oxychalcogenide Nanosheet: Facile Synthesis, Characterization, and Photodetector Application

Abstract: New 2D bismuth oxychalcogenide nanosheets have excellent theoretical properties such as high electronic mobility and excellent oxidation resistance, which have good application prospective for optoelectronic devices. In this paper, during the synthesis process via mild hydrothermal route, ammonium bismuth citrate (C6H13BiN2O7·H2O) is selected as Bi source. Both Bi2O2S and Bi2O2Se nanosheets (lateral size: over 2.0 µm, thickness: ≈ 5.0 nm) are synthesized successfully using thiourea (CH4N2S) as S source, and so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 38 publications
4
40
0
Order By: Relevance
“…However, many oxychalcogenide compounds are actually prepared by classical solid-state reactions . A number of other approaches also have been used to synthesize oxychalcogenide compounds, such as soft-chemistry, solvothermal synthesis, ,, thin-film growth, high-pressure synthesis, ion exchange, and topotactic reductive transformation . Different approaches have to be chosen according to the properties of the precursors.…”
Section: Resultsmentioning
confidence: 99%
“…However, many oxychalcogenide compounds are actually prepared by classical solid-state reactions . A number of other approaches also have been used to synthesize oxychalcogenide compounds, such as soft-chemistry, solvothermal synthesis, ,, thin-film growth, high-pressure synthesis, ion exchange, and topotactic reductive transformation . Different approaches have to be chosen according to the properties of the precursors.…”
Section: Resultsmentioning
confidence: 99%
“…The CMS condition in the hydrothermal method is unfavorable for BiONO 3 , [ 52 ] so the transformation process will be accelerated. Liu et al [ 54 ] recently reported the hydrothermal synthesis of Bi 2 O 2 Se nanosheets using ammonium bismuth citrate as the Bi source, and the organic ions can promote the formation of thinner nanosheet. These wet‐chemical synthetic procedures are simple and easy to scale up, but the agglomeration and nonuniformity are usually accompanied.…”
Section: Preparation Methodsmentioning
confidence: 99%
“…85 Analogously, Ghosh et al 3À will bind Bi 3+ on the Bi-rich (001) plane, which limits the diffusion between layers along c-axis direction, and facilitates the growth along lateral direction, resulting in the formation of thinner and larger nanosheets. 86 Although hydrothermal synthesis has the advantages of low cost and high yield, the control over lateral size and thickness of 2D Bi 2 O 2 X is still unsatisfactory. This issue may be solved by referring to the experience of successfully preparing large-size ultrathin Te flakes via hydrothermal synthesis, that is, controlling the specific growth direction of the precursor.…”
Section: Hydrothermal Synthesismentioning
confidence: 99%
“…Currently, many 2). 76,83,85,86,97,[126][127][128][129][130][131][132][133][134][135][136][137] Yan and coworkers fabricated near-infrared photodetectors based on 2D Bi 2 O 2 S flakes prepared by hydrothermal synthesis (Figure 11(A)). 85 The photodetector exhibited pronounced photoresponse under 785 nm light illumination with various power densities from 0.05 to 500 mW cm À2 (Figure 11(B)).…”
Section: Photodetectormentioning
confidence: 99%